Numerical simulation and experimental investigation of heat transfer performance of turbine blade with ribbed channel - LI Haofan; YUN Xue (Xibei Gongye Daxue Xuebao, 2023)
A combination of numerical simulation and experimental test is carried out, and the vortex core visualization technology is adopted to visualize vortex in the flow field and study the heat transfer mechanism. The heat transfer characteristics of air flow in 45° ribbed straight channel with aspect ratio of 1 and the other 6 new ribbed channels are studied. The results show that the average heat transfer performance of the new ribbed channel with all the fins 3.8 mm cut at the far end of fins along the flow direction is the best by comparing with the original ribbed straight channel under the same conditions. The average Nu, the average Nu/Nu0 and the average heat transfer enhancement factor FT of the ribbed wall is increased respectively by 25.1%, 24.8%, 22.7% on the average by comparing with the original ribbed channel. The experimental results show that the error between the experimental value and the simulated is about 10% for the outer wall temperature of ribbed channel.